2013
DOI: 10.1002/jbmr.2051
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Weight, Height, and Body Mass Index With Fracture Risk at Different Sites in Postmenopausal Women: The Global Longitudinal Study of Osteoporosis in Women (GLOW)

Abstract: Low body mass index (BMI) is a well-established risk factor for fracture in postmenopausal women. Height and obesity have also been associated with increased fracture risk at some sites. We investigated the relationships of weight, BMI, and height with incident clinical fracture in a practice-based cohort of postmenopausal women participating in the Global Longitudinal study of Osteoporosis in Women (GLOW). Data were collected at baseline and 1, 2, and 3 years. For hip, spine, wrist, pelvis, rib, upper arm/sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
164
6
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(194 citation statements)
references
References 46 publications
13
164
6
11
Order By: Relevance
“…The lower the weight and height, the greater the odds of low BMD and low femoral neck geometry and strength, respectively. These results are not surprising, given that low body weight is a known risk factor for low BMD [49] and fracture [55]. Possible reasons for the direct relation between body weight and bone health include greater mechanical force on the bone during weight-bearing activities and greater production of hormones with higher bodyweight [49].…”
Section: Discussionmentioning
confidence: 83%
“…The lower the weight and height, the greater the odds of low BMD and low femoral neck geometry and strength, respectively. These results are not surprising, given that low body weight is a known risk factor for low BMD [49] and fracture [55]. Possible reasons for the direct relation between body weight and bone health include greater mechanical force on the bone during weight-bearing activities and greater production of hormones with higher bodyweight [49].…”
Section: Discussionmentioning
confidence: 83%
“…79 The GLOW study recently showed that the relationship between fracture and weight, BMI and height is surprisingly site-specific. 82 Thus, whereas BMI showed a significant inverse association with hip, clinical spine and wrist fractures, weight was ignificantly associated with the risk of malleolar fractures. For upper arm/shoulder and clavicle fractures, only linear height was significantly associated.…”
Section: Body Mass Indexmentioning
confidence: 92%
“…Further suggestions are nutritional deficiencies of protein or vitamin D, decreased padding over the greater trochanter or a greater liability to fall. 15,82 The association between BMI and fracture risk is complex, differs across skeletal sites and is modified by the interaction between BMI and BMD.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…In particular, recent studies have shown that an increased abdominal fat tissue could be considered a risk factor for bone loss and osteoporosis [95][96][97]. Interestingly, in men obesity correlates with hypogonadism, changes in body composition, glucose tolerance alteration, increased cardiovascular risk factors, and osteoporosis [46], strongly suggesting the lack of gender-specific events.…”
Section: Obesity and Bone Metabolism: Energy Homeostasis Hormone Bomentioning
confidence: 99%